Metallocatanionic vesicle-mediated enhanced singlet oxygen generation and photodynamic therapy of cancer cells. Issue 13 (9th March 2022) - Sharma, Bunty; Jain, Akhil; Pérez-García, Lluïsa; Watts, Julie A.; Rawson, Frankie J.; Chaudhary, Ganga Ram; Kaur, Gurpreet
Abstract : In this work, dual-charge stable metallocatanionic vesicles are synthesized and used for methylene blue (MB) delivery with enhanced singlet oxygen generation capability and phototoxicity effect against cancer cells. Abstract : In clinics, photodynamic therapy (PDT) is established as a non-invasive therapeutic modality for certain types of cancers and skin disease. However, due to poor water solubility, photobleaching, and the dark toxicity of photosensitizers (PSs), further developments are required to improve the efficiency of PDT. Herein, we report the role of metallocatanionic vesicles (MCVs) in enhancing the phototoxicity of methylene blue (MB) against cancer cells. These MCVs were prepared via a facile and quick solution–solution mixing method using a cationic single-chain metallosurfactant (FeCPC I) in combination with anionic sodium oleate (Na Ol). For singlet oxygen ( 1 O2 ) generation and PDT studies, two fractions of FeCPC I : Na Ol, i.e., 30 : 70 (V37) and 70 : 30 (V73), were chosen based on their long-term stability in aqueous media. A cationic PS MB was loaded into these vesicles. The MB-loaded MCV 30 : 70 and 70 : 30 fractions enhanced the 1 O2 generation by 0.10- and 0.40-fold, respectively, compared with MB alone. Upon illumination using a 650 nm laser, these MB-loaded V73 and V37 MCVs significantly decreased the metabolic activity of MCF-7 cells by ≤50% at a concentration of 0.75 μM. Furthermore, the SOSG assay revealed that the synthesized MCVs enhanced the intracellular 1 O2 compared with MB alone. The MB-loaded V73 MCVs showed the highest 1 O2 -mediated membrane damage and cell-killing effect, as confirmed using the differential nuclear staining assay (DNS), which is attributed to the cellular uptake profile of the different MCV fractions. Altogether, this work shows the advantage of using these biocompatible and dual-charge MCVs as promising delivery vehicles that can enhance the 1 O2 generation from the PS. This work suggests the future application of these Fe-MCVs in magnetically guided PDT.